Paving the Way for Sustainability: A Study on Porous Asphalt Mixtures Reinforced with LDPE Plastic Waste and Freshwater Mussel (Pilsbryoconcha Exilis) Shell Filler - Syahbana, Mahdi; Rachman, Firmansyah; Syammaun, Tamalkhani; Munada, Fajri (International Journal of Integrated Engineering, 2024)
This study aimed to explore the impact of different fillers, namely conventional (stone ash) and alternative (mussel shell powder), along with varying percentages of Low-Density Polyethylene (LDPE) additives, on the performance of porous asphalt mixtures. The Marshall Stability and Flow of asphalt mixtures were examined with LDPE percentages of 0%, 2%, 4%, and 6%. Results highlighted that the choice of filler and LDPE content significantly influences the mixture's stability and flow. A shift from 100% stone ash to 50% mussel shell powder resulted in a slight decrease in stability for 0% and 2% LDPE, whereas for 4% and 6% LDPE, the stability was notably higher with the inclusion of the alternative filler. Mixtures with 100% stone ash exhibited increased flow values with rising LDPE concentrations, while mixtures with 100% mussel shell powder showed an opposite trend. Furthermore, mixtures containing mussel powder generally had higher flow values than those with stone ash at similar LDPE percentages. The study underscores the intricate relationship between filler types and LDPE additives in influencing the properties of asphalt mixtures. These findings pave the way for the potential use of alternative fillers in asphalt mixtures, emphasizing the importance of understanding material interactions for optimal pavement design.